(3QSGdI aj eYfi GdMOjKs - (3TeS GdOjf CHh YHO Gddg eMeO Hf NdjaI Hf SYO GdOjf GdeQMhej GdThHQj GdTGaYj, GdThHQjs
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY dCgd GdYde ebGeG hfTQ dge ai GdNGabjf CYdGeG hRci dge CMdGeG s
(3BNQgG (B:s
(3hdjcf gPG BNQ gPg GdQSGdI GdeHGQcI hGdMeO ddg GdPi HfYeJg JJe GdUGdMGJ s
(3Vef eLehY , JQJjHgG (B: 1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdMOjK h GdeUWdMs